AlfaCAD: Priročnik za osnovno uporabo - Skrinar, Matjaž (University of Maribor Press, 2020)
AlfaCAD: Basic User’s Guide. AlfaCAD is a program for static analysis of plane line structures. Although it is an older computer program that is quite functionally limited compared to modern programs, are these limited capabilities the main advantage for those users who are just beginning to use computer programs for finite element analysis. Although modern analysis programs offer significantly more options, they also require a much more experienced user who is able not only to provide the correct input data, but is able to make critical evaluations based on engineering judgment and experience about the fairness of the results obtained. Experience shows that the end result of the ability to use the programs is better if the students use simpler tools in the initial phase, where they first thoroughly acquire basic skills, and begin using the more sophisticated tools after gaining experience and confidence. The basic guideline for the preparation of this manual was therefore primarily to present the possibilities of using the program through its practical use.